Making waves: Water-soluble polymers in the aquatic environment: An overlooked class of synthetic polymers?. (15th August 2020) - Huppertsberg, Sven; Zahn, Daniel; Pauelsen, Frances; Reemtsma, Thorsten; Knepper, Thomas P.
Abstract: Synthetic polymers have been one of the defining environmental topics of the last decade. Synthetic polymers in the environment are usually classified by their size. They encompass the widely discussed size fractions of macroplastic, microplastic, and nanoplastic. Water-soluble polymers (WSPs), however, are mostly absent in this discussion. In this paper, we argue that WSPs are produced in large quantities and have many applications that facilitate a discharge into the environment, where their fate and impact remain mostly unclear. We argue that there are yet no suitable analytical methods for the quantification of WSPs in environmental matrices and propose an analytical method that utilizes size exclusion chromatography - mass spectrometry to detect and potentially also quantify WSPs through specific fragments generated by in-source fragmentation. With the detection of polyethylene glycol in a wastewater treatment plant effluent and a surface water sample we provide a first prove of principle for the applicability of this novel analytical approach to WSPs. Ultimately, we conclude that WSPs are currently in a similar position as MP were in the advent of their investigation: We know of an environmental contamination but are uncertain of its extent and impact and still lack the tools to investigate them thoroughly. Graphical abstract: Image 1 Highlights: WSP are high volume chemicals. Applications of WSP facilitate discharge in the environment. Environmental data for WSP still scarce. There are no established trace analytical methods for WSP in the environment. Development of a new approach for the detection of WSP as sum parameter is required.